SaintMary's Redcliffe
Built to house the relics of a saint , this entrance to a provincial church is also typical of the decorated age. There is no echo of the Norse about the spatial interweaving of the foliage and the figures, which is most distinctly Gothic , but little of this sort of carving was to follow. The plagues cut down the number of masons skilled enough to execute such highly decorative work, and in later years a simpler Geometric ornament was applied.